1989
DOI: 10.1029/ja094ia04p03670
|View full text |Cite
|
Sign up to set email alerts
|

Processes responsible for the compositional structure of the thermosphere

Abstract: A diagnostic postprocessor analysis package used with runs of the National Center for Atmospheric Research thermospheric general circulation model (NCAR‐TGCM) has been extended to include the terms of the neutral composition equation that is solved by this model. The purpose of the development of this capability is to quantify the relative importance of the various physical and chemical mechanisms that force changes in neutral thermospheric composition for given geophysical situations. Such mechanisms include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 73 publications
4
97
0
Order By: Relevance
“…Molecular and eddy diffusion were included in all runs. In this way we can understand how the diffusive and advective terms interact [see Burns et al, 1989] to cause the winter helium bulge. Inherently, there will be nonlinear interactions between terms in the minor species equation.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Molecular and eddy diffusion were included in all runs. In this way we can understand how the diffusive and advective terms interact [see Burns et al, 1989] to cause the winter helium bulge. Inherently, there will be nonlinear interactions between terms in the minor species equation.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Hagan [1993] and Buonsanto and Witasse [1999] used Millstone Hill radar data to show that there were small changes in meridional winds in the daytime over a solar cycle. Seasonal changes in neutral composition are driven primarily by changes in the neutral winds [Mayr et al, 1978;Burns et al, 1989]. Burns et al showed that the winds that blew through a constant pressure surface, which respond to changes in the latitudinal and longitudinal gradients of the horizontal winds, were the major source of changes in neutral composition.…”
Section: Discussionmentioning
confidence: 99%
“…But the winds also control the composition. The horizontal winds are not the main driver for composition changes, rather it is the vertical winds that blow through pressure surfaces [Burns et al, 1989]. Downward winds enhance the relative abundance of the light species like O, whereas upward winds enhance heavy species like N 2 .…”
Section: 1002/2013ja019552mentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute and relative changes in T n over the values relevant to It is well-known (e.g. Burns et al, 1989) that the thermosphere becomes more (less) molecular at a fixed pressure level when T n increases (decreases). Figure 6 shows the corresponding increases in the MMM both in absolute and relative terms for the two conditions shown in Fig.…”
Section: The Effects Of Enhanced Joule Heatingmentioning
confidence: 99%